Study on the extraction and stability of total flavonoids from Millettia speciosa Champ - Junhai Liu; Xiaosha Guo; Tengteng Yang; Xiaoli Wang; Yinku Liang (PLoS ONE, 2025)
Millettia speciosa Champ, a member of the Leguminosae family and the genus Millettia, is a rich source of total flavonoids. Investigating the extraction methods and stability of total flavonoids from Millettia speciosa Champ using ultrasound-assisted extraction is crucial for enhancing its medicinal value and advancing the modernization of traditional Chinese medicine. In this study, the optimal extraction conditions were determined as follows, ethanol volume fraction of 64%, ultrasonic temperature of 60°C, solid-liquid ratio of 1:20 g/mL, ultrasonic time of 29 min, and ultrasonic power of 400 W. Under these conditions, the extract of total flavonoids from Millettia speciosa Champ was 6.485%. The stability of the total flavonoids was evaluated under various conditions. The results indicated that the total flavonoids should be stored in the dark. Metal ions such as K+, Na+, Ca2+, Mg2+, and Al3+ had no significant impact on stability, whereas Cu2+, Zn2+, and Fe3+ caused a notable loss of stability. The total flavonoids remained stable under neutral and weakly acidic conditions but were unstable under strongly acidic and alkaline conditions. Additives such as sodium benzoate, sodium chloride, glucose, and sucrose did not significantly affect stability. In contrast, ascorbic acid and citric acid had minimal effects on stability at low concentrations but significantly impacted stability at higher concentrations.